Unemployment and Nonemployment: Heterogeneities in Labor Market States - Jones, Stephen R. G; Riddell, W. Craig (The Review of Economics and Statistics, 2006)
The determination of how to distinguish between unemployment and nonparticipation is important and controversial. The conventional approach employs a priori reasoning together with self-reported current behavior. This paper employs an evidence-based classification of labor force status using information about the consequences of the behavior of the nonemployed. We find that marginal attachment—defined as desiring work, although not searching—is a distinct labor market state, lying between those who do not desire work and the unemployed. Furthermore, important heterogeneities exist within these nonemployment states. Two subsets of nonparticipants—both engaged in waiting—display behavior similar to the unemployed.